Respuesta :
Answer:
Step-by-step explanation:
12(5+2y)=4y-(6-9y)
Distribute
12*5 +12*2y = 4y - 6 +9y
60 +24y = 4y - 6 +9y
Combine like terms
60+24y =13y -6
Subtract 13 y from each side
60 +24y-13y=13y-13y -6
60+11y = -6
Subtract 60 from each side
60+11y-60 =-6 -60
11y = -66
Divide by 11
11y/11 = -66/11
y =-6
Check
12(5+2(-6))=4(-6)-(6-9(-6) )
12 (5-12) = -24 - (6+54)
12(-7) = -24 -60
-84 = -84
True so the solution is correct
Answer: y=-6
Work shown and check solution is in the picture!
Happy mathing!
![Ver imagen chrisgibbons123lol](https://us-static.z-dn.net/files/d3a/a8d38d393e56ca3d35c9860ec7f9a72c.jpg)